Difference between Uric Acid and Albumin Levels in Chronic Kidney Failure Patients Before and After Hemodialysis : Perbedaan Kadar Asam Urat dan Albumin Pada Pasien Gagal Ginjal Kronik Sebelum dan Sesudah Hemodialisis - Maha, Maha; Puspitasari, Puspitasari (Medicra (Journal of Medical Laboratory Science/Technology), 2022)
Chronic kidney failure (CKF) is a decrease in kidney function has decreased. The impact that occurs is the accumulation of metabolic waste, including fluid overload, uremia, hyperuricemia and hyperkalemia. Hemodialysis is the process of cleansing the blood through a distillation process outside the body using a machine (dialyzer). The purpose of this study was to determine the differences in uric acid levels and albumin levels in patients with chronic renal failure before and after hemodialysis at Dr. Muhammad Zyn Sampang General Hospital. This type of research is experimental with 15 patients using purposive random sampling technique. The method of examining uric acid using Enzymatic Photometry, and the method of examining albumin using Bromocresol Green. The research was conducted in April-May 2021 at RSUD Dr. Muhammad Zyn Sampang. This study used the Wilcoxon test. It can be concluded that there is a significant difference (p <0.05) uric acid levels (p = 0.001) and albumin levels (p = 0.001) in patients with chronic renal failure before and after hemodialysis.